1999
DOI: 10.1016/s0896-6273(00)80831-4
|View full text |Cite
|
Sign up to set email alerts
|

Learned Movements Elicited by Direct Stimulation of Cerebellar Mossy Fiber Afferents

Abstract: Definitive evidence is presented that the conditioned stimulus (CS) in classical conditioning reaches the cerebellum via the mossy fiber system. Decerebrate ferrets received paired forelimb and periocular stimulation until they responded with blinks to the forelimb stimulus. When direct mossy fiber stimulation was then given, the animals responded with conditioned blinks immediately, that is, without ever having been trained to the mossy fiber stimulation. Antidromic activation was prevented by blocking mossy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 31 publications
7
98
1
Order By: Relevance
“…Consistent with previous studies, mossy fiber stimulation supported robust learning (Fig. 5, top) (n ϭ 4; F (4,12) ϭ 18.2; p Ͻ 0.001) (Steinmetz et al, 1989;Hesslow et al, 1999). In an initial test session to confirm proper cannula placement, we infused muscimol to silence the AIN.…”
Section: Experiments 2: the Site Of Plasticity Underlying Slrs Is Upstsupporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with previous studies, mossy fiber stimulation supported robust learning (Fig. 5, top) (n ϭ 4; F (4,12) ϭ 18.2; p Ͻ 0.001) (Steinmetz et al, 1989;Hesslow et al, 1999). In an initial test session to confirm proper cannula placement, we infused muscimol to silence the AIN.…”
Section: Experiments 2: the Site Of Plasticity Underlying Slrs Is Upstsupporting
confidence: 85%
“…5). Therefore, both SLRs and normal conditioned responses are learned during red nucleus inactivation (Krupa et al, 1993) and with mossy fiber stimulation as the CS (Steinmetz et al, 1989;Hesslow et al, 1999). [It is unlikely that plasticity in a pathway downstream of the AIN that initially bypasses the red nucleus (e.g., via thalamus, cortex, and back to red nucleus) or presynaptic plasticity (e.g., increased transmitter release) in the red nucleus mediates SLRs, because the threshold for evoking eyelid closure by stimulating the AIN does not change with training (Tracy et al, 1998).]…”
Section: Experiments 5: Slrs Are Learned and Associativementioning
confidence: 99%
See 1 more Smart Citation
“…However, this observation is contradicted by recent studies, which have revealed short-latency responses after lesion or reversible disconnection of the cerebellar cortex and thus suggest that lesions that completely abolish conditioned responses may have involved inadvertent damage to the interpositus nucleus (Perrett et al, 1993;Perrett and Mauk, 1995;Garcia and Mauk, 1998;Garcia et al, 1999). Cerebellar nucleus plasticity mediated by the mossy fiber input has also been disputed on the basis that strong mossy fiber stimulation fails to elicit short-latency responses (Hesslow et al, 1999). It remains possible, however, that background Purkinje cell activity was able to suppress short-latency responses in this experiment and that evidence for short-latency responses would have been observed had the mossy fibers been stimulated during disconnection of the cerebellar cortex.…”
Section: Discussionmentioning
confidence: 93%
“…Arguments have been presented suggesting that a second site of plasticity outside the cerebellar cortex is not necessary for the expression of conditioned responses or at least that plasticity does not occur in the cerebellar nucleus (Yeo et al, 1985;Hesslow et al, 1999). Cerebellar nucleus plasticity is disputed by observations that lesions of the cerebellar cortex can abolish the expression of previously learned responses (Yeo et al, 1985).…”
Section: Discussionmentioning
confidence: 99%